(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the mathematical creative thinking abilities of students at SMP Negeri 2 Kota Pontianak in solving problems on quadrilaterals, including squares, rectangles, trapezoids, and parallelograms. The study uses a case study approach with a descriptive qualitative method. The research subjects were all 30 students in class VII C. Data were collected through a mathematical creative thinking ability test and interviews to deepen understanding of the students’ thinking processes. The data obtained were analysed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that students’ mathematical creative thinking skills were divided into three categories, namely high category with 4 students (13.33%), medium category with 22 students (73.33%), and low category with 4 students (13.33%). These findings indicate that the majority of students are in the medium category, meaning that they are already capable of demonstrating basic creativity but still need guidance to develop more original ideas, think flexibly, and elaborate their answers more completely